Surgical Results in Unilateral Superior Oblique Muscle Palsy - Aylin Tenlik; Yaşar Duranoğlu; Hatice Deniz İlhan (Türk Oftalmoloji Dergisi)
Objectives: To evaluate the surgical treatments and results of the patients with superior oblique muscle palsy (SOMP). Materials and Methods: Clinical charts of the patients with unilateral SOMP who were operated in our clinic between 1999 and 2009 were evaluated retrospectively. Patients’ demographics, preoperative signs, surgical procedure, complications, and final results were recorded. Results: Thirty-seven patients were included in the study, [21 (59%) male, 15 (41%) female]. The mean age was 20.6 years at the time of operation. The mean time interval between diagnosis and operation was 7.3 years. Postoperative follow-up period was 2.04 (ranging 1-10) years. Diplopia was determined in seven (18.9%) patients, and abnormal head position in 36 (97.3%) patients. Only inferior oblique tenotomy with distal muscle resection was performed in 25 patients. In addition, five patients had recession of the contralateral inferior rectus muscle and two patients had recession of the ipsilateral superior rectus muscle additional to inferior oblique tenotomy. Abnormal head position was completely improved in all of the patients postoperatively. The preoperative average score of the inferior oblique muscle (IOM) overaction was +3.3±0.8, and postoperative overaction was found in only two patients (+1.5). There was statistically significant difference between the two periods (p<0.001). The average score of the superior oblique muscle hypofunction was -2.18 preoperatively, and in only three patients, the score was found -1.0 postoperatively. Difference between the two periods was statistically significant (p<0.001). While the preoperative average vertical deviation was 22 PD in primary position, none of the patients had hyperdeviation postoperatively. Diplopia was resolved in all seven affected patients postoperatively. Contralateral IOM hyperfunction was the most common complication (13.5%). Adherence syndrome was seen in none of the patients. Conclusion: It was found that to weaken the IOM solely was satisfactory in the patients with hyperdeviation secondary to unilateral SOMP in this study. (Turk J Ophthalmol 2014; 44: 293-6)